Long‐Term Effects of Self‐Administered Transcranial Direct Current Stimulation in Episodic Migraine Prevention: Results of a Randomized Controlled Trial - Pohl, Heiko; Moisa, Marius; Jung, Hans‐H.; Brenner, Kathrin; Aschmann, Jessica; Riederer, Franz; Ruff, Christian C.; Schoenen, Jean; Luechinger, Roger; Widmer, Lukas; Petersen, Jens A.; Gantenbein, Andreas R.; et al. (Neuromodulation (Malden, Mass.), 2021)
Background Migraine is a multifactorial neurovascular disorder, which affects about 12% of the general population. In episodic migraine, the visual cortex revealed abnormal processing, most likely due to decreased preactivation level. Transcranial direct current stimulation (tDCS) is able to modify cortical excitability and might result in an alleviation of migraine occurrence if used repetitively. Objective To test the hypothesis that self‐administered anodal tDCS over the visual cortex significantly decreases the number of monthly migraine days in episodic migraine. Materials and Methods The study was single‐blind, randomized, and sham‐controlled. Inclusion criteria were age 18–80 years and an ICHD‐3 diagnosis of episodic migraine. Exclusion criteria were pregnancy, presence of a neurodegenerative disorder, a contraindication against MRI examinations, and less than two migraine days during the 28‐day baseline period. Patients in whom the baseline period suggested chronic migraine were excluded. After baseline, participants applied daily either verum (anodal‐1 mA to 20 min) or sham tDCS (anodal‐1 mA to 30 sec) at Oz (reference Cz electrode) for 28 days. Headache diaries were used to record the number of migraine days at baseline, during the stimulation period, and during four subsequent 28‐day periods. Results Twenty‐eight patients were included; two were excluded after the baseline period because less than two migraine days occurred; three were excluded because their headache diaries suggested the diagnosis of chronic migraine. Twenty‐three datasets were taken for further analysis. Compared to sham tDCS (n = 12), verum tDCS (n = 11) resulted in a lower number of migraine days (p = 0.010) across all follow‐up periods. We found no significant change in total headache days (p = 0.165), anxiety (p = 0.884), or depression scores (p = 0.535). No serious adverse events occurred; minor side effects were similar in both groups. Conclusions This study provides Class II evidence that self‐administered anodal tDCS over the visual cortex in episodic migraine results in a significantly lower number of monthly migraine days. However, it has neither an immediate nor a long‐term effect.